Apocalyptic Diversity, Demonic Anthropology, and the Evangelical Ēthnos: Modes of Imagining Difference among American Charismatic Evangelicals1. Issue 2 (October 2016) - Bialecki, Jon
Abstract: How do American Charismatic Evangelicals imagine human difference? Ethnographic fieldwork with the Vineyard, a Southern California originated but now nation‐wide Charismatic Evangelical movement, suggests that for many lay American Charismatic Evangelicals, difference is conceptualized in three different modes, involving potentialities, relations, and boundedness. Much like a grammar shapes communication without imposing a single meaning, these forms of conceiving human difference mandate no single intrinsic political position, but do affect the way that American Charismatic evangelicals express and contest notions of human difference.